A Primer on Underwater Quantum Key Distribution - Paglierani, Pietro; Fahim Raouf, Amir Hossein; Pelekanakis, Konstantinos; Petroccia, Roberto; Alves, João; Uysal, Murat (Quantum engineering, 2023)
The growing importance of underwater networks (UNs) in mission-critical activities at sea enforces the need for secure underwater communications (UCs). Classical encryption techniques can be used to achieve secure data exchange in UNs. However, the advent of quantum computing will pose threats to classical cryptography, thus challenging UCs. Currently, underwater cryptosystems mostly adopt symmetric ciphers, which are considered computationally quantum robust but pose the challenge of distributing the secret key upfront. Post-quantum public-key (PQPK) protocols promise to overcome the key distribution problem. The security of PQPK protocols, however, only relies on the assumed computational complexity of some underlying mathematical problems. Moreover, the use of resource-hungry PQPK algorithms in resource-constrained environments such as UNs can require nontrivial hardware/software optimization efforts. An alternative approach is underwater quantum key distribution (QKD), which promises unconditional security built upon the physical principles of quantum mechanics (QM). This tutorial provides a basic introduction to free-space underwater QKD (UQKD). At first, the basic concepts of QKD are presented, based on a fully worked out QKD example. A thorough state-of-the-art analysis of UQKD is carried out. The paper subsequently provides a theoretical analysis of the QKD performance through free-space underwater channels and its dependence on the key optical parameters of the system and seawater. Finally, open challenges, points of strength, and perspectives of UQKD are identified and discussed.